Implementasi Supervisi Akademik untuk Meningkatkan Profesionalisme Guru di MAN 2 Magelang - Syaiful Faizin (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
This scientific work aims to describe (1) the efforts of teachers at MAN 2 Magelang in developing professionalism, (2) the efforts of MAN 2 Magelang in enhancing teacher professionalism, and (3) the factors inhibiting the development of teacher professionalism at MAN 2 Magelang. This study employs a descriptive-qualitative approach. Data collection methods include interviews, observations, and document analysis. Data analysis is conducted using a descriptive-qualitative method. The results of the research indicate that (1) efforts by teachers to develop professionalism at MAN 2 Magelang include pursuing further studies at the Master's level by 6 teachers (12%), professional certification by 24 teachers (48%), participation in self-development by 23 teachers (46%), conducting scientific publications and innovative work by 9 teachers (18%), personality and social competencies have reached 80%, and library visits have reached 100%; (2) efforts by the madrasah in enhancing teacher professionalism at MAN 2 Magelang (external factors) are still low, with no encouragement for skill improvement through further studies, participation in scientific meetings and professional development, enhancement of knowledge through additional learning resources, or teacher development through supervision by the madrasah principal and supervisors; (3) inhibiting factors include (a) external factors, such as the role of madrasah leadership in the teacher professionalism development program not being optimal and budget constraints, and (b) internal factors, such as the low interest and motivation of teachers to participate in professionalism development efforts initiated by the madrasah, especially in programs for participation in scientific meetings in the form of MGMP, professional development in the form of publications, and utilization of the madrasah library collection, even though only 4 teachers or 8% are considered mismatched Abstrak Penulisan karya ilmiah ini bertujuan untuk mendeskripsikan (1) upaya guru MAN 2 Magelang dalam mengembangkan profesionalisme, (2) upaya MAN 2 Magelang dalam mengembangkan profesionalisme guru, dan (3) factor penghambat dalam pengembangan profesionalisme guru MAN 2 Magelang. Penulisan karya ilmiah ini menggunakan pendekatan deskriptif-kualitatif. Metode pengumpulan data dengan wawancara, observasi, dan dokumen. Analisis data dengan deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa (1) upaya guru dalam pengembangan profesionalisme di MAN 2 Magelang melalui studi lanjut S2 sebanyak 6 orang (12%), guru professional yang lulus sertifikasi sebanyak 24 orang (48%), guru yang mengikuti pengembangan diri sebanyak 23 orang (46%), guru yang melaksanakan publikasi ilmiah dan karya inovatif sebanyak 9 orang (18%), kepribadian dan social sudah mencapai 80%, kunjungan perpustakaan mencapai 100%; (2) upaya madrasah dalam pengembangan profesionalisme guru di MAN 2 Magelang (faktor eksternal) masih rendah, belum ada dorongan peningkatan keahlian melalui studi lanjut, dorongan keikutsertaan dalam pertemuan ilmiah dan pengembangan profesi, peningkatan pengetahuan melalui penambahan referensi sumber belajar, pembinaan guru melalui supervisi oleh kepala madrasah dan pengawas madrasah; (3) faktor penghambat adalah (a) faktor eksternal, yaitu peran pimpinan madrasah dalam program pengembangan profesionalisme guru belum optimal dan keterbatasan anggaran madrasah, dan (b) faktor internal, yaitu minat dan motivasi guru untuk mengikuti pengembangan profesionalisme yang diupayakan pihak madrasah masih kurang, terutama dalam program pengembangan keikutsertaan dalam pertemuan ilmiah dalam bentuk MGMP, pengembangan profesi dalam bentuk karya, dan pemanfaatan koleksi buku di perpustakaan madrasah, padahal guru yang mismatch hanya 4 orang atau 8% saja